Molecular Epidemiology of Rotavirus Strains in Symptomatic and Asymptomatic Children in Manhiça District, Southern Mozambique 2008–2019 - Filomena Manjate; Eva D. João; Percina Chirinda; Marcelino Garrine; Delfino Vubil; Nélio Nobela; Karen Kotloff; James P. Nataro; Tacilta Nhampossa; Sozinho Acácio; Jacqueline E. Tate; Umesh Parashar; et al. (Viruses, 2022)
Group A rotaviruses remain the leading cause of diarrhoea in children aged <5 years. Mozambique introduced rotavirus vaccine (Rotarix®) in September 2015. We report rotavirus genotypes circulating among symptomatic and asymptomatic children in Manhiça District, Mozambique, pre- and post-vaccine introduction. Stool was collected from enrolled children and screened for rotavirus by enzyme-immuno-sorbent assay. Positive specimens were genotyped for VP7 (G genotypes) and VP4 (P genotypes) by the conventional reverse transcriptase polymerase chain reaction. The combination G12P[8] was more frequently observed in pre-vaccine than in post-vaccine introduction, in moderate to severe diarrhoea (34%, 61/177 vs. 0, p < 0.0001) and controls (23%, 26/113 vs. 0, p = 0.0013) and mixed genotypes (36%, 24/67 vs. 7% 4/58, p = 0.0003) in less severe diarrhoea. We observed changes in post-vaccine compared to pre-vaccine introduction, where G3P[4] and G3P[8] were prevalent in moderate to severe diarrhoea (10%, 5/49 vs. 0, p = 0.0002; and 14%, 7/49 vs. 1%, 1/177, p < 0.0001; respectively), and in less severe diarrhoea (21%, 12/58 vs. 0, p = 0.003; and 24%, 14/58 vs. 0, p < 0.0001; respectively). Our surveillance demonstrated the circulation of similar genotypes contemporaneously among cases and controls, as well as switching from pre- to post-vaccine introduction. Continuous surveillance is needed to evaluate the dynamics of the changes in genotypes following vaccine introduction.